The 2011 Egyptian Revolution and Islamists in Egypt and Malaysia: Similar Goals, Different Circumstances (American Journal of Islam and Society, 2013)
The opposition Islamist PAS (Parti Islam Se-Malaysia, or PanMalaysian Islamic Party) is one of the oldest political parties inMalaysia. Inspired by Egypt’s Ikhwan al-Muslimin (MuslimBrotherhood [MB]), PAS is also influenced by occurrences in theMiddle East; following the 1979 Iranian Revolution, its leadersrevamped their organizational structure to entrust key decisionsto religious scholars. The ramifications of the 2011 Egyptian revolution,arguably one of the most significant Middle Eastern politicalevents in recent times, thus deserves a closer look.This short article attempts to look at this revolution’s possible impacton Islamists in Malaysia. I argue that Malaysia had alreadyundergone its own version of a revolution in the 1998 reformasi(reformation) due to the shared characteristics between the twoevents: both (1) shared the same premise of alleged political injustice;(2) provided opportunities for Islamists to influence thepolitical discourse, with the difference that in Egypt there was apolitical vacuum; and (3) utilized the Internet heavily to rally themasses. However, due to Malaysia’s freer democratic and electoralprocesses, political changes there will not be as abrupt as inEgypt. Furthermore, both Egypt’s revolution and Malaysia’s reformasihave hardly ended; the former is a tumultuous ongoingprocess of battling for the legitimacy of rule by appealing to themasses, while the latter is an ongoing process of appealing to votersin order to come to rule.